Strategi Pengembangan Sektor Industri Kreatif Dalam Mendorong Pertumbuhan Ekonomi Nasional - Agus Wahyudi; Gresceilla Septiarini Anwar; Octavia Nuril Kamila; Danisa Rada Silviana (Lembaga Pengembangan Kinerja Dosen, 2024)
The creative industry sector has become one of the important contributors to national economic growth in many countries. This research aims to explore development strategies for the creative industry sector in Indonesia in order to encourage national economic growth. Using qualitative methods of literature study, this research analyzes various secondary data sources, including government reports, scientific journals, and publications related to the creative industry. The research findings reveal the great potential that Indonesia has in the creative industry sector, such as rich culture and diversity of creative resources. However, there are challenges that must be faced, such as the lack of supporting infrastructure, access to capital, and protection of intellectual property rights. This research proposes a development strategy that includes identification of leading subsectors, increasing competitiveness and innovation, as well as targeted government policies and support. By implementing this strategy, Indonesia can take advantage of the creative industries sector as a driver of sustainable economic growth and increase competitiveness in the global market.